(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article synthesizes research and practice-oriented guidance on teaching English to preschool and early primary learners (approximately ages 4–10) in foreign-language contexts. Using a scoping review strategy, it maps evidence on developmentally appropriate pedagogy (play, stories, songs, movement, and classroom routines), comprehensible input and interactional scaffolding, vocabulary growth and formulaic language, early literacy and phonics, and formative assessment. The synthesis indicates that an early start alone does not guarantee higher proficiency; outcomes depend on time-on-task, quality of input, and opportunities for meaningful use and spaced recycling (Cameron, 2001; Muñoz, 2006; Pinter, 2017). Effective programs integrate multimodal experiences, short cycles of retrieval practice, and supportive use of learners’ first language to sustain comprehension and confidence. Based on converging findings, the article proposes an applied framework for teachers and curriculum designers: plan around communicative functions and routines before grammatical labels; select high-frequency lexical targets and ensure repeated retrieval across modalities; align phonological awareness, phonics, and emergent literacy to children’s cognitive readiness; assess through observable performance using simple rubrics and portfolios; and involve families through achievable home micro-tasks. Implications are discussed for teacher training, classroom management, and equitable learning in resource-constrained settings.